Evaluation of local tissue peri-implant reaction in total knee arthroplasty failure cases. (May 2022) - Brozovich, Ava; Clyburn, Terry; Park, Kevin; Harper, Katharine D.; Sullivan, Thomas; Incavo, Stephen; Taraballi, Francesca
Introduction: Implant-related hypersensitivity is emerging as a causative factor as a potential source of total knee arthroplasty (TKA) failure. Mechanistically, this type IV hypersensitivity reaction (T4HR) is mediated by effector T-cells, macrophages, and leukocytes that infiltrate to the site of implant and react to metal exposure and induce inflammatory tissue damage. Methods: A case–control study was performed where cortical bone was taken at the time of revision surgery for all patients operated on for primary TKA in which metal allergy was suspected and for revision TKA cases done for presumed metal allergy. Cytof was used to determine the cell density of inflammatory cells, specifically Th1, Th2, M1, and M2 cells. Results: Comparing the mean cell density of primary versus revision TKA, revision TKA patients had significantly higher number of Th2 cells compared with Th1 cells ( p = 0.0043). Among revision cases, there were significantly more M1 versus M2 macrophages ( p = 0.034) within a patient. When comparing mean cell density of M1 versus M2 macrophages, there was a significant difference in both primary and revision TKA surgeries ( p = 0.0041 primary, p < 0.001 revision). Among revision patients who had a predominance of Th2 cells, four (44%) of nine patients had a negative LTT/patch test. Conclusion: These data support metal hypersensitivity, mediated by a T4HR, for some cases of TKA failure. Current methods to screen patients for metal hypersensitivity prior to primary TKA have been inclusive. This study demonstrates the need for a more sensitive screening test from specimens in the knee joint, to more accurately identify patients who will exhibit a T4HR to metal.